(3QaY GdOGaYjI ddJYde dOi CWaGd GdCSQ GdeaccIs - (3GdNGdOj, efi hdjO GdNWjHs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2013)
(3JJHfi gPg GdOQGSI eTcdI GdOGaYjI GdefNaVI ddJYde dOi YTQ JdGejP ef eOQSI YcG GdGHJOGFjI hgj EMOi eOGQS GdCfQhG dJYdje GdWdGH GddGLFjf GdadSWjfjjf aj UjOG(B. (3hJgOa GdOQGSI Edi eYGdLI cjajI GSJKGQI GdOGaYjI ddJYde ef NdGd eQMdJjf(B: (3eQMdI OQGSI GdCSHGH heQMdI eYGdLJgG ef NdGd HQfGeL EQTGOj eJNUU(B. (3aj GdeQMdI GdChdi Je GSJNOGe YOI COhGJ dLeY GdeYdheGJ hJMdjdgG dcTa GdCSHGH, hgj(B: (3GdebGHdI eY GdeQTOI hHYV CaQGO GdWGbe GdeOQSj, GdSLdGJ GdJQGcejI ddCWaGd hedGMXI Sdhcge aj GdeOQSI(B. (3h bO NdUJ gPg GdeQMdI Edi JMOjO GdeTcdGJ GdJj jYGfj efgG GdJdGejP hGdfGJLI Yf GfNaGV JhGabge GdfaSj hGdeYQaj(B. (3hef gPg GdeTcdGJ GdSdhc GdeOQSj ZjQ GdShj GdfGHY ef GfNaGV JbOjQ GdPGJ cGdJfeQ hGdYOhGf hGdNha hGdNLd HGdEVGaI Edi GdeTcdGJ GdCSQjI habOGf GdGgJeGe hGdCeGf hJOfj GdJTLjY Ydi GdJYde hGdeKGHQI(B.(3aj GdeQMdI GdKGfjI bGe GdeDda HhVY HQfGeL EQTGOj jJe JWHjbg Ydi Tcd CfTWI EQTGOjI Vef YOI eLGdGJ ddCOGA efgG GdEYdGej hefgG GdGLJeGYj hGdJMUjdj heYXegG ebGHdGJ aQOjI EQTGOjI, hLeYjI, hfTGWGJ dGUajI ddJdGejP bjO GdOQGSI HgOa JMbjb GQJaGmY fSHmj aj GdOGaYjI GdJYdejI dOjge(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Children; Enfants; Milieu Socio-Culturel Motivation; Socio-Cultural Milieu Motivation; (3GdCWaGds; (3GdhSW GdKbGaj GdGLJeGYj GdOGaYjIs